The technology for producing clarified butter (Ghee) using vacuum evaporation - Dovhal, Yevhen (Запоріжжя: ТДАТУ, 2026)
Clarified butter is a concentrated milk fat with high nutritional value, good digestibility, and enhanced stability during storage. Thanks to the almost complete removal of moisture, lactose, and protein components, the product has a long shelf life and is resistant to microbiological spoilage. The quality of clarified butter is determined by processing temperature and the method of fat-phase dehydration.
Keywords: milk; clarified butter